Evaluation of Social Media and Students Participation in Politics: A Study of Students in the University of Nigeria, Nsukka - Isaac, Dorathy; Azubuike, Chieme (European Scientific Journal, ESJ, 2019)
The emergence of social media has made it quite easy for students to participate in political matters. However, it has been observed that most youths use social media to participate in politics in ways that promote political violence and tension in the country. It is on this basis that this work set out to examine, amongst others, the extent of usage of social media by the undergraduate students of UNN in politics. The Uses and Gratification theory was the theoretical framework of this study. The survey research design was adopted for the study and a total of 375 respondents served as the sample size of the study. Among other findings, the research discovered that the respondents are highly exposed to social media and that they use social media to a high extent to participate in politics. Hence, some of the following recommendations were proffered. Tertiary institutions must make it their responsibility to train and produce students that are conscious of their activities and actions in ways that promote peace and unity in the nation. This could be achieved by conducting periodic seminars before, during, and after elections to educate and enlighten the students on the dangers associated with the dysfunctional use of the social media in participating in politics. Students and the general public should self-regulate their use of social media in participating in politics. This can be achieved by asking themselves if the ways they use social media are ethical and for the general good of all.